TINGKAT KEPUASAN PASIEN RAWAT INAP TERHADAP PROGRAM KELAS RAWAT INAP STANDAR (KRIS) DI RSUD dr. GONDO SUWARNO UNGARAN BARAT KABUPATEN SEMARANG - Nadhira Giani Putri; astuti Astuti (Journal of Politic and Government Studies, 2026)
The implementation of the Standard Inpatient Class (KRIS) is an Indonesian government policy designed to promote equitable healthcare services by replacing the previous BPJS inpatient class system. The effectiveness of this policy should be evaluated from the perspective of service recipients through patient satisfaction assessment. This study aims to analyze the satisfaction level of National Health Insurance (JKN) inpatients toward the implementation of the KRIS program at RSUD dr. Gondo Suwarno, West Ungaran, Semarang Regency, and to examine the findings through the Good Governance perspective. A descriptive quantitative approach with a survey method was employed involving 100 JKN inpatients selected using purposive sampling. Data were collected through structured questionnaires and analyzed using the Community Satisfaction Index (Indeks Kepuasan Masyarakat/IKM) based on the Decree of the Minister for Administrative Reform Number KEP/25/M.PAN/2/2004, consisting of fourteen service elements. The findings indicate an overall IKM score of 86,93, categorized as Grade A (Excellent Service Quality). All service elements achieved mean scores above 3.25. Staff responsibility received the highest score (3.55), while ability of the officer (3.44). The Good Governance analysis demonstrates that the principles of transparency, accountability, effectiveness and efficiency, equity, responsiveness, and participation have been reflected in the implementation of the KRIS program, although several administrative and human resource aspects still require improvement. This study concludes that the implementation of the KRIS program at RSUD dr. Gondo Suwarno has achieved a very high level of patient satisfaction while reflecting the application of Good Governance principles. Continuous improvements in administrative procedures, service schedule certainty, staff discipline, and staff competency remain necessary to sustain healthcare service quality.